2021
DOI: 10.4102/sajim.v23i1.1283
|View full text |Cite
|
Sign up to set email alerts
|

The influence of demographic factors on perceived risks affecting attitude towards online shopping

Abstract: Background: Online shopping adoption has been rising in South Africa (SA). However, there is still a large majority of consumers who are not buying online because of certain risks associated with online shopping. This is despite the fact that internet adoption has increased and is widely accessible by the majority of South African consumers.Objectives: The purpose of this study was to determine the risk factors that influence consumers’ attitude towards online shopping in SA. Furthermore, the study aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
(29 reference statements)
0
10
0
1
Order By: Relevance
“…Lian & Yen (2014) indicated that the major factors propelling older customers to online shopping were performance expectation and social influence as for younger customers too; on the other hand, the major barriers included value, risk, and tradition which differed from younger customers. According to Makhitha & Ngobeni (2021), the relationships between product, security and privacy risks, and attitude towards online shopping were moderated by age. Results of Soopramanien (2011) found that younger consumers are more likely to express a positive attitude towards online shopping compared with older consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lian & Yen (2014) indicated that the major factors propelling older customers to online shopping were performance expectation and social influence as for younger customers too; on the other hand, the major barriers included value, risk, and tradition which differed from younger customers. According to Makhitha & Ngobeni (2021), the relationships between product, security and privacy risks, and attitude towards online shopping were moderated by age. Results of Soopramanien (2011) found that younger consumers are more likely to express a positive attitude towards online shopping compared with older consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Nittala (2015), "perceived risk and price positively influenced online shopping behavior, whereas positive attitude, product risk, and financial risk affect negatively online shopping behavior" (p. 38). Consumer attitudes towards online shopping are more impacted by privacy and security risk (Makhitha & Ngobeni, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Meskipun perusahaan berusaha sebaik mungkin untuk memuaskan pelanggan mereka, masih saja sederetan resiko yang membayangi pelanggan untuk enggan membeli secara online karena kekhawatiran mereka tentang privasi dan keamanan transaksi online (Makhitha & Ngobeni, 2021), juga beberapa konsumen mengkhawatirkan tidak menerima pesanan mereka, dan juga prihatin tentang kesulitan mengenai proses pengembalian, serta faktor-faktor yang terkait dengan pencurian identitas, penipuan dan keamanan. Ini adalah faktor risiko itu memengaruhi sikap konsumen terhadap belanja online.…”
Section: Faktor-faktor Penghambat Belanja Onlineunclassified
“…In the modern world, the popularity of the internet is increasing rapidly [27][28][29] as a result, companies have started investing hundreds of millions of dollars in efforts to establish an electronic presence on the internet [30]. Accordingly, this vital emphasis on the rapid development of the internet has drastically modified the lives of consumers around the world and played an essential role in globalizing and changing the consumer buying process [28,31]. For example, the expansion of online shopping has provided customers the option to easily compare product characteristics and prices, making it the most flexible way of purchasing [32].…”
Section: Introductionmentioning
confidence: 99%
“…[87]), and consumer's adoption (e.g. [28,[88][89][90][91]). There are also studies conducted on consumer's continuance, for example, Gidey [34].…”
mentioning
confidence: 99%